Increased prevalence and coincidence of antinuclear and antithyroid antibodies in the population exposed to high levels of polychlorinated pollutants cocktail - Cebecauer, L.
Výskum vplyvu znečisťujúcich prvkov na zdravie človeka. Výskum. Predmet. Metódy. Výsledky. Diskusia.